1879 Mich. Pub. Acts 43-44, Local Acts, An Act To Amend . . . An Act To Incorporate The Village Of Constantine, § 12 - (:unkn) unknown (General Publisher, 1879)
The common council shall have full power and authority to . . . regulate the keeping and sale of gunpowder in said village[.]
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER